Urteilen und Werten: Interdisziplinäre Perspektiven auf narrative Axiologien - Burghardt, Anja; Scholz, Nora (transcript, 2021)
The study of the judgement inherent in every narrative is the most important contribution that narrative research can currently make to public debates.